1994
DOI: 10.1126/science.8303299
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Lectin-Like Activity of Tumor Necrosis Factor

Abstract: Tumor necrosis factor (TNF), but not lymphotoxin (LT), is directly trypanolytic for salivarian trypanosomes. This activity was not blocked by soluble 55-kilodalton and 75-kilodalton TNF receptors, but was potently inhibited by N,N'-diacetylchitobiose, an oligosaccharide that binds TNF. Comparative sequence analysis of TNF and LT localized the trypanocidal region, and synthetic peptides were trypanolytic. TNF molecules in which the trypanocidal region was mutated or deleted retained tumoricidal activity. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
259
1
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 175 publications
(272 citation statements)
references
References 29 publications
10
259
1
2
Order By: Relevance
“…In mammals, TNF-␣ has been shown to directly bind to the variant specific glycoprotein present in the flagellar pocket of some African trypanosomes and to cause direct lysis (31)(32)(33)(34). An invertebrate functional analog of mammalian TNF-␣, named coelomic cytolytic factor (CCF-1), has been described in the earthworm Eisenia foetida foetida (78).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, TNF-␣ has been shown to directly bind to the variant specific glycoprotein present in the flagellar pocket of some African trypanosomes and to cause direct lysis (31)(32)(33)(34). An invertebrate functional analog of mammalian TNF-␣, named coelomic cytolytic factor (CCF-1), has been described in the earthworm Eisenia foetida foetida (78).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether the lectin-like activity ascribed to mammalian TNF-␣, and known to act through its TIP domain (31,32), would be conserved in the homologous carp TNF-␣ molecule. The ability of carp TNF-␣1 and TNF-␣2 to kill the bloodstream form of T. brucei (AnTat 1.1 clone) was investigated in a trypanolytic assay.…”
Section: Lectin-like Activity Of Carp Tnf-␣mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the VSG molecule plays a critical role in antigenic variation and because of the ability of the trypanosome to evade host immune responses during infection, we previously asked whether there was an association between expressed VSG molecules and virulence levels in the T. brucei rhodesiense LouTat 1 serodeme. Our preliminary observations, as well as unrelated studies by others (Musoke and Barbet, 1977;Mathias et al, 1990;Lucas et al, 1994;Magez et al, 1997Magez et al, , 1998, suggested that the VSG molecule could play a direct role in the relative expression of trypanosome virulence expression for a host. This suggestion was derived from our observation that all daughter cell trypanosome populations that expressed elevated virulence in an infected host were derived from a less-virulent trypanosome parent cell population that expressed a surface coat distinct from each of the virulent populations (Inverso and Mansfield, 1983).…”
Section: ; De Lange Andmentioning
confidence: 69%
“…Therefore, we initially hypothesized that trypanosome virulence may be determined directly by the VSG molecule itself. Such an hypothesis has an experimental basis because VSG molecules and their substituents have been shown to express or induce biological activities independent of their status as variant antigens (Musoke and Barbet, 1977;Mathias et al, 1990;Lucas et al, 1994;Magez et al, 1997Magez et al, , 1998Coller et al, 2003;Leppert et al, 2007;Lopez et al, 2008). Alternatively, we proposed that the expression of virulence may be linked to the ES utilized by VSG genes.…”
Section: Introductionmentioning
confidence: 97%